Automation in Construction: an Exploration of Emerging Technologies for the Nigerian Construction Industry - Jalam, Abdurrahman Aliyu; Keftin, Namala Amuga; Abdullahi, Umar; Yayajo, Sakinatu Muhammad; Datti, Usman Mohammed; Saleh, Ibrahim Mallam (Darul Yasin Al Sys, 2024)
This study explores the potential of emerging technologies aiming to transform the Nigerian construction industry. The technologies offer innovative solutions to persistent challenges such as inefficiencies, project delays, cost overruns, and safety risks. The Nigerian construction industry (NCI) is, however, reluctant to implement the technologies because of a lack of substantive comprehension of the features of the innovative technologies. Hence, it has become necessary for the NCI to fully understand the benefits and challenges of the emerging technologies for construction project efficiency. The exploratory literature review identified and examined seventeen (17) emerging technologies, revealing sufficient practical benefits such as enhancing productivity, improving safety, saving costs, and increasing transparency. It also identifies some barriers to their adoption, such as high implementation costs, a lack of skilled professionals, resistance to change, and a technological knowledge gap. The findings suggest that while NCI has started adopting these technologies, significant efforts are needed to address infrastructural limitations and promote skill development. The study concludes by discussing the implications of the findings for construction firms and policymakers and recommendations for future research on the adoption of automation technologies in developing economies, particularly Nigeria.